Realization of all-optical vortex switching in exciton-polariton condensates - Xuekai Ma (Nature Portfolio, 2020)
Vortices can be generated in many platforms and are useful due to manipulation of their vorticity. Here the authors show generation and optical switching of a vortex in exciton-polariton condensates using GaAs microcavities.